Microstructure and thickness of the resin cement layer at zirconia crown over titanium base interfaces: an in vitro study - Souto, Jorge Miguel Carneiro (2022)
Background: After a cementation procedure, the resin matrix cement layer can vary at the zirconia to titanium base interface of implant-supported prosthesis. Also, the roughness of the inner zirconia and titanium base surfaces do affect such resin-matrix cement layer variation. Purpose: The main aim of the present project was to evaluate the microstructure and the thickness of the resin-matrix cement layer on zirconia to titanium base interfaces over dental implant abutment. Materials and method: At first, a literature search on PubMed (via National Library of Medicine) was conducted on the articles published in the last ten years using the following search terms: “zirconia” AND “cementation” AND “titanium base” OR “titanium link” AND “abutment” AND “resin-matrix cement” OR “resin cement” AND “thickness” OR “layer”. Zirconia crowns were produced by CAD-CAM and surfaces of titanium abutment base were prepared by different techniques, namely: grit-blasting, anodization, or grit-blasting plus anodization. Details on the roughness and morphological aspects were evaluated by optical and scanning electron microscopy for the zirconia and titanium base surfaces after the surface treatment. Zirconia crowns were cemented over titanium base after the surface modification under 1kg following the manufacturer’s instructions. Groups of specimens were cross-sectioned for morphological evaluation. Then, the microstructure and thickness of the resin-matrix cements at the zirconia to titanium base interfaces was carefully analyzed by microscopic inspection. Results: The surface of the titanium based was significantly modified by grit-blasting or anodization procedures leading to an increased roughness and therefore retention for cementation using resin-matrix cements. The thickness of resin-matrix cement ranged from around 15 up to 150 µm within the crown-to-titanium base interfaces. The margin of the zirconia crowns showed the lowest mean values of resin-cement thickness than those recorded along the restoration. Macro-scale defects such as voids and pores were detected at the resin-matrix cement layer as well as thick layers of adhesive. Conclusions: The surface modification of titanium base abutment increase the roughness and retentive area for cementation. Nevertheless, the thickness of the resin-matrix cement and adhesive layers significantly varies at the titanium base to zirconia crowns manufactured by CAD-CAM. Defects in the resin-matrix cement layer can be spots for failures by propagation of cracks and catastrophic fracture.